PELATIHAN PUBLIC SPEAKING DAN OPINI PUBLIK BAGI LURAH/ SEKRETARIS LURAH DAN APARAT KECAMATAN ABELI KOTA KENDARI - Joko Joko; La Ode Muh. Umran; St. Harmin; La Ode Jumaidin; Muh. Rajab (Jurnal Pengabdian NUSANTARA, 2022)
The purpose of this writing is to find out and provide an understanding of Public Speaking Training And Public Opinion For Lurah/Lurah Secretary And Abeli District Apparatus Kendari City. The method is through training, workshops, mentoring and evaluation as a concrete form of community service activities. The results of research and Community Service in Abeli District, Kendari City, are that village officials in Namnbo District, Kendari City can do things such as understand the other person, write material in the form of bullet points, insert humor and rhetorical questions, look at the person he is talking to, speak directly. slowly, and practice in front of a mirror and other people in order to develop public speaking and invite public opinion. Some of the obstacles experienced by the lurah apparatus in Nambo Subdistrict include forgetting self-potential, dimming self-confidence, and not mastering material content.